A revised model of salinity surface reflection coefficient at a range of frequencies - Elmutasim, Imadeldin Elsayed; Mohamad Shaiful, Abdul Karim; Izzeldin Ibrahim, Mohamed Abdelaziz; Bilal, Khalid Hamid; Hassan, Mohamed (JES, 2024)
The frequency of the incident signal wave can affect how salinity influences the seawater's reflection coefficient. The impact of salinity on the electromagnetic characteristics of seawater is generally more pronounced at multiple frequencies. This paper investigates a wide range of frequencies such as 100 MHz up to 1 THz under the 30 ppt salinity level, angle is 30-degree, distance traveled up to 100 meter, and sweater dielectric 81 to offer distinct attention that should respect each salinity value individually when designing the wireless coastal connection. Due to an undeniable disagreement among scholars regarding the relationship between salinity and frequency, the study provides a method to predict the reflection coefficient in different ranges of frequencies using derivation equations. Nevertheless, the distinct outcomes show under the 30 ppt salinity the reflection coefficient hit 0.015 dB at frequencies from 100 MHz up to 500 MHz and then growing up to reach 0.03 dB at 1 GHz, whereas under the same salinity level and from 100 GHz to 500 GHz achieved 0.2 up to 0.4 dB, and increase to hit 0.9 dB at 1 THz. The significance of the result would open the way to accommodate the salinity levels under the specific frequency and hence the accuracy of the link budget. Overall, the fluctuation in coastal link parameters such as frequency, power transmitted, and salinity level produces peculiar signal behavior that should be estimated in the coastline budget.